2017
DOI: 10.1007/s00068-017-0815-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric out-of-hospital cardiopulmonary resuscitation by helicopter emergency medical service, does it has added value compared to regular emergency medical service?

Abstract: PurposeTo determine the outcome of out-of-hospital (OOH) cardiopulmonary resuscitation (CPR) and the advanced life support (ALS) procedures provided in pediatrics by the Rotterdam Helicopter Emergency Medical Service (HEMS)MethodsRetrospective evaluation of all pediatric (0–17 years) OOH cardiopulmonary arrests within a 6-year period and attended by the Rotterdam HEMS team.ResultsThere were 201 OOH CPRs from October 2008 until October 2014. Endotracheal intubation was performed in 164 cases and done by HEMS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Caution is also needed in interpreting our metaanalysis subgroup analysis results as these are observational in nature. However, we believe that the results of the within-study comparisons of different team composition performances in four studies [8,28,32,38], together with insights from our recent study [7], are credible and supportive of higher overall intubation success, first-pass success, and lower complication rates associated with physician teams. Our results were also robust when sensitivity analysis and meta-regressions were performed.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Caution is also needed in interpreting our metaanalysis subgroup analysis results as these are observational in nature. However, we believe that the results of the within-study comparisons of different team composition performances in four studies [8,28,32,38], together with insights from our recent study [7], are credible and supportive of higher overall intubation success, first-pass success, and lower complication rates associated with physician teams. Our results were also robust when sensitivity analysis and meta-regressions were performed.…”
Section: Discussionmentioning
confidence: 70%
“…Five studies [7,8,28,32,38] compared outcomes between different intubator groups, and one study [37] described outcomes before and after implementation of national guidelines. Of the 46 described team compositions, 22 studies utilised non-physicians with no relaxants (n = 7602), 12 utilised non-physicians with relaxants (n = 2185), and 12 utilised physicians, all with relaxants (n = 1780).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a lower cancellation rate for pediatric involvement of 27% was found in another Dutch HEMS region [23]. Concerning incidents involving a child, it was shown that HEMS have an increased success rate for Advanced Life Support restricted procedures, and an additional 2.5 lives are saved per 100 dispatches [18,20,29]. However, identifying children in need of acute trauma care remains challenging, as van der Sluijs et al showed an undertriage rate of 16.3% based on data derived from several Dutch trauma regions [30].…”
Section: Incidents With Pediatric Involvementmentioning
confidence: 99%
“…Securing the airways patency in prehospital conditions may be a challenge for paramedics [1]. The endotracheal intubation still remains the golden standard, however, the use of it is limited by the necessity of having experienced medical personnel [2][3][4]. When performing the rescuing procedures by firefighters-paramedics the use of supraglottic airway devices (SADs) is a more appropriate method.…”
Section: Introductionmentioning
confidence: 99%